Problems of Legal Regulation of Cyber Violations in Kazakhstan and Ways to Eliminate Them - Mukhamedzhan, A.B.; Ibrayeva, A.S.; Assanova, S.E. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This article explores the challenges of ensuring cybersecurity and regulating cybercrime in Kazakhstan in the context of international best practices. The leading goal of the study is to identify weaknesses in national cybersecurity legislation and propose ways to enhance threat prevention by examining the experiences of the United States, the European Union, and China. The research underlines that the rising number of cybercrimes and their cross-border nature highlight the urgent need for coordinated and comprehensive legal responses. Effective legal regulation of cybersecurity is a critical factor for protecting national information security, defending citizens’ rights, and ensuring the sustainable development of the digital economy. The study analyzes significant regulatory frameworks such as the GDPR, CFAA, CLOUD Act, and China’s Cybersecurity Law, focusing on their content and implementation mechanisms. Methodologically, the research applies comparative legal and regulatory analysis. It reveals key issues, including weak coordination between state and private entities and insufficient incident response mechanisms. The article presents specific recommendations, including establishing a unified coordinating body and strengthening international cooperation. The study's findings propose a valuable contribution to improving Kazakhstan’s cybersecurity legal framework.